Thermal Design and Verification of Spherical Scientific Satellite Q-SAT - Yunhan He; Boxin Li; Zhaokui Wang; Yulin Zhang (International Journal of Aerospace Engineering)
Small satellites have gradually become an important mean of space scientific exploration. The Tsinghua University developed a spherical small satellite, Q-SAT, which is aimed at detecting the Earth gravity and atmosphere parameters. In the current paper, thermal control for Q-SAT is discussed. For heat exchange between the satellite and the environment, radiation plays the main part. Different from traditional cuboid satellites, the current spherical satellite has no individual heat input and output plane which brings challenges to the thermal design of the satellite. In addition, the cost of small satellites is required to be as low as possible. A passive thermal control solution based on integrated spherical structure is employed on the Q-SAT. The combination of two integrated hemispheres is designed to facilitate the heat conduction. Different materials are utilized to control the heat transfer path. Firstly, a set of numerical simulations demonstrate that the current design can be well adapted to complex flight environment. Next, the thermal design is verified by thermal tests. As the traditional heat radiation lamps cannot meet the test requirements of the spherical satellite, an external heat flow test method which is based on distributed heaters is proposed. Results from numerical simulations agree well with the experimental test results. Both results show that the thermal system can guarantee the functions of the satellite. Q-SAT was successfully launched into orbit on August 6, 2020. The telemetry data from Q-SAT verified the effectiveness of the satellite thermal system. The thermal design and test method proposed in present paper can potentially be adopted to other small scientific satellites as well.